Incidence of Bacteriuria after Urodynamic Study with or without Antibiotic Prophylaxis in Women with Urinary Incontinence - Elizabeth Yukie Hirakauva; AnaMaria Homem deMello Bianchi-Ferraro; Eliana Viana Monteiro Zucchi; Marcio Massashi Kajikawa; Manoel João Batista Castello Girão; Marair Gracio Ferreira Sartori; Zsuzsanna Ilona Katalin de Jarmy-Di Bella (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Introduction The presence of bacteria in urine is called bacteriuria, which may be symptomatic or asymptomatic. The manipulation of the urinary tract during urodynamic study (UDS), which is an invasive procedure, can result in urinary tract infection (UTI). Studies on the use of prophylactic antibiotics for UDSs are contradictory. Some investigators concluded that they were valuable and others did not. The objective of this study is to evaluate the efficacy of antibiotic prophylaxis before UDS. This is a placebo-control randomized double-blind study. Methods Two-hundred and seventeen women affected by urinary incontinence were eligible for this study. All patients had presented negative urine culture previous to the UDS. They were randomized in four groups: group A received placebo, group B received 500 mg of levofloxacin, group C received 80 mg trimethoprim and 400 mg sulfamethoxazole and group D received 100 mg of nitrofurantoin. A urine culture was performed 14 days after the UDS. Results We observed asymptomatic bacteriuria after the UDS in five patients in group A, one in group B, one in group C and one in group D. Only one patient on group A had symptomatic bacteriuria.We didn't observe statistical difference between the groups. When we recategorized the patients in two groups, the incidence of bacteriuria was significantly higher in the placebo group compared with the antibiotic group. Conclusion The conclusion is that antibiotic prophylaxis before the UDS did not reduce the incidence of UTI in women within the target population.